Biosynthesized Silver Nanoparticles Generated from Eucalyptus camaldulensis Show Synergistic Efficacy Against Multidrug-resistant Bacteria - Ali, Muna Jalal; AlMatar, Manaf (Current Nanoscience, 2025)
<span class=
Keywords: AgNPs